Contraintes d'utilisation des technologies de l'information géographique pour la gestion intégrée des zones côtières en Afrique - Françoise Gourmelon; Marc Robin; Jade Georis Creuseveau; Gwenaëlle Pennober; Alfredo Simao da Silva; K. Affian; C. Hauhouot; Patrick Pottier (VertigO, 2006)
Three GIS applications for african coastal environmental are presented: an observatory of coastal environmental changes in Mauritania, coastal risk assessments in Ivory Coast and a synthetic approach to the Bijagos Archipelago Biosphere Reserve in Guinea Bissau. The main steps and the results illustrate the different stages of GIS implementation (inventory, analysis and management applications). GIS capabilities for monitoring, environmental changes analysis and modelling are highlighted and discussed. But despite these obvious capabilities, it is clear that the GIS long term success will also depend on organizational and human issues.